Digital Image Data Security Using MATLAB -Based AES-128 Algorithm - Mazayah Tsaqofah; Juwita Sari; Nurhidayati; Adinda Tarisyah Hsb; Rizky Abdillah; Mrs. Rusdi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Digital images are widely used for storing and transmitting sensitive information , so that aspect data security is becoming very important. This research discuss digital image data security using the Advanced Encryption Standard (AES) algorithm with a long key 128 bit implemented in MATLAB environment. The method used is cryptography . symmetric , where the encryption and decryption processes use a key the same secret . The encryption process done to randomize the pixel value of the original image so that visual information cannot be recognized , while the decryption process aim return image encrypted to condition back to the beginning without data changes . System evaluation done through histogram analysis , process time measurement , and evaluation quality image using the Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) parameters. The test results show that The encrypted image has a random histogram pattern and does not resemble original image . In addition that , the decryption process produce MSE value of zero and PSNR value not finite , which indicates the absence of lost information . Thus , it can concluded that the MATLAB -based AES-128 algorithm is effective and reliable in improving the security of digital image data .